PENGEMBANGAN APLIKASI DATA WAREHOUSE UNTUK PENGELOLAAN SUMUR MINYAK - Mangaras Yanu F; Wilis Kaswidjanti; Bambang Yuwono; Jefri Hutama Arbi (Telematika, 2015)
Implementation of the company's activities implemented towards good governance requires a system that can accommodate the needs of the service that is fast, precise and integrated that able to support management. This study was conducted to develop applications that can accommodate needs of P.T. Geotama Energy in the operations to manage data of the oil well in the form of Data Warehouse application Interface. This application was developed with prototyping method using the programming language PHP and MySQL as a database.The results of the research is a data warehouse application interface for managing oil wells. The results of research still has limitations in the management of the data source because the application is not designed to process the input and editing of data. Kegiatan penyelenggaraan perusahaan dilaksanakan untuk menuju good governance memerlukan sistem yang mampu mengakomodir kebutuhan pelayanan yang cepat, tepat dan terintegrasi yang mampu memberi dukungan manajemen. Penelitian ini dilakukan untuk mengembangkan aplikasi yang mampu mangakomodir kebutuhan P.T. Geotama Energy dalam menjalankan usahanya untuk mgengelola data sumur minyak yang berupa Interface Data Warehouse. Aplikasi ini dikembangkan dengan metode prototyping dengan menggunakan bahasa pemrograman PHP dan MySQL sebagai database. Hasil penelitian berupa aplikasi interface data warehouse untuk pengelolaan sumur minyak berbasis web. Hasil penelitian masih memiliki keterbatasan dalam pengelolaan sumber data karena aplikasi tidak dirancang untuk proses input dan editing data.